A Chinese White Pear (Pyrus bretschneideri) BZR Gene PbBZR1 Act as a Transcriptional Repressor of Lignin Biosynthetic Genes in Fruits - Cao, Yunpeng; Meng, Dandan; Li, Xiaoxu; Wang, Lihu; Cai, Yongping; Jiang, Lan (Frontiers in Plant Science, 2020)
BZR transcription factors play essential roles in plant growth and environmental stimuli, and they are also the positive regulators of Brassinosteroid (BR) signal transduction in diverse plants. In addition, BZR TFs, as crucial regulators of BR synthesis, may have multiple stress-resistance functions and their related regulatory mechanisms have been well illustrated in model plants. Here, we carried out a genome-wide identification of BZR members in Chinese pear (Pyrus bretschneideri) and identified 13 members. By comparative analysis in five Rosaceae genomes, BZR members in the pear genome may have undergone large-scale duplication events during evolution. Purifying selection played an important role in almost all of the orthologous and paralogous gene pairs. According to the expression analysis of the PbBZRs during fruit development, three PbBZRs were selected for detailed analysis. Transcriptional activation assays presented that PbBZR1 repressed the promoters of P. bretschneideri lignin biosynthetic genes, such as PbCES9, PbCOMT3 and PbHCT6. Our study traces the evolution of BZR gene family members in Rosaceae genomes and illustrates that the rates of gene loss and gain are far from equilibrium in different species. At the same time, our results suggest that PbBZR1 may be involved in the negative regulation of lignin biosynthesis.